Assessing the Oldness and Capacity of Radiography and Ultrasound Equipments in Tehran University of Medical Sciences - Salamati, Payman (Kowsar, 2013)
BACKGROUND: Maintenance of imaging equipment is a very important part of the management of all medical imaging centers. OBJECTIVES: To assess the oldness and capacity of radiography and ultrasound equipment in Tehran University of Medical Sciences. MATERIALS AND METHODS: The study was performed in 16 hospitals, 4 faculties and three healthcare centers of Tehran University of Medical Sciences. We evaluated all the X-ray equipment (including the simple plain and dental, panorex, mammography, fluoroscopy and C-arm X-Ray devices) and also simple and Doppler ultrasound machines in terms of the type and usage of the device, production year, quantity of utilization, location, brand and current condition. RESULTS: Among fixed X-ray systems, 15 were currently in use, two were junk, two were damaged, and one was not utilized. The mean (SD) of the usage of these was 2151 (2230) cliché/month, and the mean (SD) of the oldness was 16.9 (13.6) years. The oldness of radiography equipment in our study was more than 20 years in 16, between 11 and 20 in 46, and less than 10 years in 76 devices. The mean (SD) usage (patients/month) of simple and color Doppler devices were 234.1 (365.2) and 597.5 (505.3), respectively. The oldness of ultrasonography equipment in our study was more than 11 years in 12 and less than 10 years in 55 devices. We found that 22 (15.9%) of the radiography systems and two (3%) of the ultrasonography systems had been used for more than 20 years. CONCLUSION: Radiology equipment in Tehran University of Medical Sciences have potential capacity, but they need repair, and better maintenance and management and application of standards for the imaging system needs organized supervisory mechanisms.